(4x+1)÷3+(2x-1)÷2-(3x-7)÷5=6 solve the equations
Answers
Answered by
44
(4x+1)/3 + (2x-1)/2-(3x-7)/5=6
Taking LCM of 3,2,6 we get 6
(4x+1)/3 × 6+(2x-1)/2× 6 -(3x-7)/ 5 × 6=6×6
2(4x+1)+3(2x-1)-6(3x-7)/5=36
8x+2+6x-3-(18x-42)/5=36
14x-1-18x+42=36×5
-4x+41= 180
-4x=180-41
x= 139/-4
x= -34 whole 3 by 9
Hope it helps
☺☺☺
Taking LCM of 3,2,6 we get 6
(4x+1)/3 × 6+(2x-1)/2× 6 -(3x-7)/ 5 × 6=6×6
2(4x+1)+3(2x-1)-6(3x-7)/5=36
8x+2+6x-3-(18x-42)/5=36
14x-1-18x+42=36×5
-4x+41= 180
-4x=180-41
x= 139/-4
x= -34 whole 3 by 9
Hope it helps
☺☺☺
Answered by
88
Answer:
The image attached below has the answer.
Attachments:
![](https://hi-static.z-dn.net/files/d60/a7d6e6ce210ad02d3cccddfddffcd3fe.jpg)
Similar questions